Satisfaction Index and Prioritizing the Factor of Students’ Satisfaction Towards UTHM Hostel in Pagoh - Woon, Yee Ying; Sufahani, Suliadi Firdaus (Enhanced Knowledge in Sciences and Technology, 2026)
Hostel experience plays an important role to improve student’s academic performance and increase university’s popularity. This study aims to determine whether the UTHM students are satisfied with the hostel UTHM in Pagoh or not and also identify the main model factors that will influence the student’s satisfaction towards the hostel. Through American Customer Satisfaction Index (ACSI), the average for all items in each satisfaction factors are calculated to measure the satisfaction index on the satisfaction level of students towards the hostel UTHM in Pagoh. In order to prioritise the factors that influence the students’ satisfaction towards the hostel, the variables with factor loadings above 0.5 are selected. In the principal component analysis (PCA), the result shows it has 2 group of factors: the availability of hostel facilities, the quality of hostel facilities and services, that will influence students’ satisfaction towards the hostel while in the factor analysis (FA), the result shows that there are 8 main factors extracted which are the accessibility of hostel, room comforts and facilities, hostel service and environment quality, additional facilities and services, study environment and student service, furniture quality, sports facilities quality and availability and the student health service. By comparing the FA and the PCA results, the factor analysis results were prioritized because they explain more variance and provide a more comprehensive satisfaction model. The ACSI score of 46.61 indicates that students are not satisfied with the UTHM hostel in Pagoh. These findings can help the university to determine students’ satisfaction levels more accurately and also prioritize the main factors influencing their satisfaction with the hostel, which can help prevent unnecessary costs. Additionally, this method can be applied in future research to assess students’ satisfaction with other aspects of the university, such as the campus facilities.